2013
DOI: 10.3390/molecules18032611
|View full text |Cite
|
Sign up to set email alerts
|

α(δ')-Michael Addition of Alkyl Amines to Dimethyl (E)-hex-2-en-4-ynedioate: Synthesis of α,β-Dehydroamino Acid Derivatives

Abstract: Abstract:The direct nucleophilic addition of alkyl amines to the α(δ')-carbon atom of dimethyl (E)-hex-2-en-4-ynedioate to generate α,β-dehydroamino acid derivatives is reported. Herein, we have studied the reactivity of various primary and secondary alkyl amines in the α-selective nucleophilic conjugate addition to conjugated dimethyl (E)-hex-2-en-4-ynedioate. The reaction with primary alkyl amines gives only the (2E,4E)-stereoisomer, while that with secondary alkyl amines gives the (2E,4E) and (2Z,4E)-stereo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 29 publications
(29 reference statements)
0
24
0
Order By: Relevance
“…The configuration of the diene was found to be ( E , E ), as reported in simple amine addition. [14a] The reaction conditions were optimized to improve the yield of the product, and only selected results are presented in Table . After extensive optimization, it was found that N ‐propargylic α‐enamino ester 3a could be obtained in 56 % yield if the reaction was performed with 2 equiv.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The configuration of the diene was found to be ( E , E ), as reported in simple amine addition. [14a] The reaction conditions were optimized to improve the yield of the product, and only selected results are presented in Table . After extensive optimization, it was found that N ‐propargylic α‐enamino ester 3a could be obtained in 56 % yield if the reaction was performed with 2 equiv.…”
Section: Resultsmentioning
confidence: 99%
“…In 2005, Ramachandran et al reported the quantitative conversion of alkyl propiolate into dialkyl ( E )‐hex‐2‐en‐4‐ynedioate by using a catalytic amount of 1,4‐diazabicyclo[2.2.2]octane (DABCO) . Dialkyl ( E )‐hex‐2‐en‐4‐ynedioate underwent α‐addition regioselectively upon reaction with amine nucleophiles . Chuang and co‐workers reported many interesting synthetic methods involving the use of a PPh 3 nucleophile for the α‐addition to diethyl ( E )‐hex‐2‐en‐4‐ynedioate .…”
Section: Introductionmentioning
confidence: 99%
“…1]) . Various nucleophiles (amines,, alcohols,,, thiols, thioureas, purine, and thymine) have been used in the intermolecular α‐addition towards alkynoates after Trost's pioneering contribution. To the best of our knowledge, however, only three examples have been reported in the literature using α‐addition of amides towards alkynamides [Scheme , Eqs.…”
Section: Methodsmentioning
confidence: 99%
“…however, they exhibit variable Z selectivities. [229][230][231][232][233] Furthermore, Ooi described in 2018 a spectacular organocatalysed 1,6-Michael addition of azlactones (235) to enynyl N-acyl pyrazoles (236). [234] The use of a P-spiro chiral triaminoiminophosphorane catalyst not only allows the perfect control of the addition regioselectivity (1,6 vs 1,4), but also the Z,Econfiguration of the diene and the enantioselectivity of the quaternary centre in the resulting compounds (237, Scheme 92).…”
Section: Organocatalysed 16-michael Additionsmentioning
confidence: 99%